2019
DOI: 10.1108/ijppm-05-2018-0199
|View full text |Cite
|
Sign up to set email alerts
|

Mediation effects financial performance toward influences of corporate growth and assets utilization

Abstract: Purpose The purpose of this paper is to measure the effects of corporate financial performance toward the influences of corporate growth and company asset utilization on the corporate market value. Design/methodology/approach This research is an explanatory research that describes the influences of one or more variables on other variables based on secondary data. This research took place in Indonesia and was carried out from 2011 to 2016. Findings The findings of this study are corporate growth has a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 23 publications
2
34
0
5
Order By: Relevance
“…For control variables, this study measured five factors: Revg, Rdd, Bnig, Oeg and Ard (see Table 1), is found by previous studies that may determine firm value (Boisjoly et al, 2020;Rahayu, 2019;Sardo & Serrasqueiro, 2018;Zeidan & Shapir, 2017). Lastly, we control for quarterly fixed as well as industry differences in our sample.…”
Section: Measure Of Variablesmentioning
confidence: 99%
“…For control variables, this study measured five factors: Revg, Rdd, Bnig, Oeg and Ard (see Table 1), is found by previous studies that may determine firm value (Boisjoly et al, 2020;Rahayu, 2019;Sardo & Serrasqueiro, 2018;Zeidan & Shapir, 2017). Lastly, we control for quarterly fixed as well as industry differences in our sample.…”
Section: Measure Of Variablesmentioning
confidence: 99%
“…Control variables. Previous studies found the following control variables affected EP: growth rate of revenue (GRR) stands for "the percentage increases in revenue quarter over the quarter"; current ratio (CR) stands for "current assets divided by current liability"; net profit growth rate before taxes (NPGBT) refers as "net profit before taxes for the current period minus net profit before tax of the previous period divided by net profit before tax of the previous period"; the growth rate of owner's equity (GROE) is "owners' equity of current period minus owners' equity of previous period divided by owners' equity of previous period" (Rahayu, 2019;Sardo and Serrasqueiro, 2018;Zeidan and Shapir, 2017); average collection days (ARD) (Boisjoly et al, 2020;Teng et al, 2021;Zeidan and Shapir, 2017) and firm size (SIZE) is the book value of total assets and is measured by the natural logarithm of total assets (Lee and Xiao, 2021;Song et al, 2021).…”
Section: Ijchm 342mentioning
confidence: 99%
“…Investment decisions are critical to a corporation's goal of maximisation of shareholders' wealth (Singh et al, 2012;Mangesti Rahayu, 2019). In particular, research and development (R&D) investments enhance a firm's competitiveness and technological capabilities (Dong and Gou, 2010;Shaikh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, besides the static relationship, it also considers the dynamic relationship between corporate governance and corporate investments. Finally, this study attempts to address how corporate governance may influence a firm's value by evaluating its implications on the investment decisions that have been shown to be an important determinant of its valuation (Singh et al, 2012;Mangesti Rahayu, 2019).…”
Section: Introductionmentioning
confidence: 99%